The Influence of Technology Acceptance Model (TAM) on Disaster Management in Indonesia via The Twitter Platform - Ahmad Bastomi; Anjar Priyono (PT SOLUSI EDUKASI BERDIKARI, 2024)
The rapid progress of information technology systems influences disaster management, for example Twitter is used in Indonesia for disaster management. The purpose of this research is to determine the influence of technology with the variables subjective norm, image, output quality, result demostrability, perceived usefulness, perceived ease of use, use of Twitter, information accessibility, adaptability, resilience, and proactiveness to provide an overview of the disaster management situation. The research was conducted using a questionnaire method and convenience sampling technique on Twitter social media users, obtaining 150 respondents. The research applies the PLS-SEM version 4.0.9.9 SmartPLS method. The research results show that all research variables have a positive effect on disaster management. The research carried out can provide an overview of the disaster management situation by utilizing technological information.